Ekspertni pristup poboljšanju sigurnosti u zonama radova na cesti - Vrkljan, Joso (Array, 2018)
An ever-increasing volume of traffic on Croatian roads increases the volume of maintenance work. Road works negatively impact traffic mobility and road user safety, and also safety of the maintenance workers. Improving traffic mobility and safety is the key issue that all interested parties (planning and managing road works and those executing them) should address. Mitigation of negative effects is possible via certain expert system measures. Presented in the paper are the options provided by expert systems implemented in the road work zones as factors for improving road maintenance and safe traffic flow, as well as road workers safety. Introducing relevant data into the data base, an expert system is created providing the driver approaching a road work zone with a number of alternative routes. Also shown is a driving diagram for road work zones with special focus on slowing down speed upon entering the road work zone. The results show that the implementation of expert systems based on relevant data would significantly facilitate traffic management in road work zones and improve the safety of traffic and road workers, as well as the workers' efficacy.